(untitled) (Strathmore Law Journal, 2023)
In the history of ideas, few institutions are as important or are as closely related as Family, Property, and Inheritance, for the establishment and function of an ordered society. About them, many perspectives have been taken by legal and political thinkers and philosophers on both the traditional Catholic and libertarian schools and their contemporary variants, which coincidentally agree that all of them are products of a perennial order, in most cases of a spontaneous origin that manifests itself within Natural Law, and as such, must be protected by positive legislation, although its relation is always understood as one of logic and not one of institutions. On the other hand, an opposing and hostile perspective on Family, Property, and Inheritance is promoted by revolutionary Marxism, revealing that, at least on its negation, there is a universal outlook on the mutual need of these three institutions to subsist as part of the social order, and particularly, as legal institutions, which uses, and formal aspects are protected by legislation to be applied in a particular community. By exploring these stances, as well as the proper definitions of Civilization, and order, one may understand the meaning of family, private property, and inheritance, as well as their legal conceptions in the history of ideas, and the way they are universally opposed by the Marxist schools of thought, based on their own revolutionary ends.